A Case Study of the Use of Newsela PRO Among Adult, Emergent Bi/Multilingual Learners in a Precollege Program. Issue 2 (May 2021) - Housel, David A.; Oranjian, Nevair
Adult literacy and English as an Additional Language (EAL) programs are often challenged to find suitable and authentic reading texts and instructional materials for their students. Newsela PRO, an entirely online resource, provides high-interest fiction, timely news articles, and other nonfiction texts in both English and Spanish that focus on developing reading and critical thinking skills by providing students with five levels of reading difficulty. Although originally designed for younger learners, the use of Newsela PRO has recently expanded into adult literacy programs. This convergent mixed-methods study investigated the usability and instructional use of this educational technology in an intensive, precollege EAL program in a community college in the northeastern United States. This case study found that instructors felt the detailed reports provided by Newsela PRO enhanced their instruction and feedback and enabled them to differentiate instruction more effectively. Regardless of language-proficiency level, students found Newsela "easy to very-easy-to-use." They were motivated to read more extensively and developed more confidence in their academic skills and English-language proficiency. These preliminary findings justify the additional cost of Newsela PRO as well as exploring its expanded use in other adult education, EAL, and literacy programs, especially Spanish-language literacy programs, both in the United States and internationally. As many adult and higher education programs were mandated to transition to distance learning exclusively during the recent COVID-19 pandemic, the effective instructional use of educational technology has become critical.